2013
DOI: 10.17129/botsci.10
|View full text |Cite
|
Sign up to set email alerts
|

Variación genética en poblaciones mexicanas de  Swietenia macrophylla  King, una especie tropical en expansión geográfica reciente.

Abstract: 2 Autor para la correspondencia: dvalerio@umich.mx.Resumen: Swietenia macrophylla King, es una especie tropical que históricamente ha sido explotada por su alta calidad maderable y actualmente está catalogada como amenazada de extinción. En este estudio se usaron cuatro microsatélites nucleares polimórfi -cos para estimar los niveles de variación y estructura genética de seis poblaciones fragmentadas de S. macrophylla, distribuidas en la Península de Yucatán y sur de Veracruz, México. Se encontró un promedio d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
1
2
2
1
Order By: Relevance
“…Overall, our results were similar to those reported for other Mexican populations of Swietenia macrophylla sampled within the Yucatan peninsula and analyzed with microsatellite loci. For example, Trujillo-Sierra et al (2013) reported from 21 to 26 alleles per population (29 alleles in total), whereas 25 alleles were reported in this study (in the group of adults for comparison). Mean values of the observed heterozygosity (H O ) of 0.420 and 0.410 has been reported respectively by Trujillo-Sierra et al (2013) and by Alcalá et al (2014), which coincide with our estimate of 0.451.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Overall, our results were similar to those reported for other Mexican populations of Swietenia macrophylla sampled within the Yucatan peninsula and analyzed with microsatellite loci. For example, Trujillo-Sierra et al (2013) reported from 21 to 26 alleles per population (29 alleles in total), whereas 25 alleles were reported in this study (in the group of adults for comparison). Mean values of the observed heterozygosity (H O ) of 0.420 and 0.410 has been reported respectively by Trujillo-Sierra et al (2013) and by Alcalá et al (2014), which coincide with our estimate of 0.451.…”
Section: Discussioncontrasting
confidence: 70%
“…For example, Trujillo-Sierra et al (2013) reported from 21 to 26 alleles per population (29 alleles in total), whereas 25 alleles were reported in this study (in the group of adults for comparison). Mean values of the observed heterozygosity (H O ) of 0.420 and 0.410 has been reported respectively by Trujillo-Sierra et al (2013) and by Alcalá et al (2014), which coincide with our estimate of 0.451. These two studies also showed a statistically signifi - cant deviation of the genotypic frequencies, revealing a high coeffi cient of fi xation (0.309 and 0.449, respectively).…”
Section: Discussioncontrasting
confidence: 70%
“…Although the current forest management model incorporates the concept of reduced impact logging (RIL), it has been criticized for promoting the reproductive isolation of species and favoring non-random mating, which may contribute to increases in inbreeding and lead to genetic erosion. This is particularly this case for species such as S. macrophylla that generally present a low density (< 1 tree/ha) in natural populations (André et al, 2008;Sebbenn et al, 2008;Lacerda et al, 2013;Trujillo-Sierra et al, 2013;Alcalá et al, 2015). Genetic studies have reported that S. macrophylla has high levels of genetic diversity and differentiation among populations in areas without logging (Lemes et al, 2003;Degen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have reported that S. macrophylla has high levels of genetic diversity and differentiation among populations in areas without logging (Lemes et al, 2003;Degen et al, 2013). Although the species may be self-incompatible (Bawa et al, 1985), studies based on genetic markers as microsatellite loci have reported a loss of genetic diversity and increased inbreeding as a result of forest fragmentation and logging of its natural habitat (André et al, 2008;Sebbenn et al, 2012;Breed et al, 2012;Degen et al, 2013;Trujillo-Sierra et al, 2013). The juveniles assigned with estimates of genetic diversity and structure, inbreeding, pollen dispersal, and mating patterns can be used as additional measures to inform sustainable forest management practices and help to understand the impacts of forest management on the spatial genetic structure (SGS) of managed species (Gillies et al, 1999;Lourmas et al, 2007;Sebbenn et al, 2012;Baldauf et al, 2013;Degen et al, 2013;Lacerda et al, 2013;Vinson et al, 2015Vinson et al, , 2018Arruda et al, 2015;Dal Bem et al, 2015;Duminil et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Los datos obtenidos sugieren que existe una diferenciación genética alta (Fst = 0,419), lo cual concuerda con otros estudios realizados en C. odorata en Costa Rica y Perú donde han reportado una alta diferenciación genética entre poblaciones (Gillies et al 1997, De la Torre et al 2008, así como niveles de diversidad altos (Cavers et al 2003). Para la especie de la misma familia Swietenia macrophylla, que también ha sufrido sobreexplotación, se reporta una variación genética moderada (He = 0,600) aunque un nivel de endogamia alto y significativo (Fis = 0,309) y una diferenciación genética baja pero significativa con una Fst de 0,095 (Trujillo-Sierra et al 2013). En los resultados del presente estudio se obtuvo un nivel de endogamia similar al trabajo anterior (Fis = 0,306), aunque con una variación genética baja (He = 0,261), en contraste a lo reportado por otros autores en donde la heterocigosidad esperada indicó una variación genética alta (He = 0,820 Figura 1.…”
Section: Discussionunclassified